Identification of Pups and Yearling Wolves by Dentine Width in the Canine - Parker, G.R.; Maxwell, J.W. (ARCTIC, 1986)
One hundred and thirty-nine wolf (Canis lupus) skulls and mandibles were collected from hunters and trappers of northern Quebec and Labrador during the winters of 1980-81 through 1983-84. The maximum width of the dentine-cementum wall in wolf canine teeth was used to separate pups killed late in their first year from yearlings killed early in their second winter of life. Both age classes may have a closed foramen at the apex of the root and a clear deposit of cementum with no opaque annulus.Key words: wolf (Canis lupus), canine teeth, dentine width, pups versus yearlings Mots clés: loup (Canis lupus), canines, épaisseur de la dentine, louveteaux contre loups âgés d'un an